How I treat a first single seizure in a child - Gulati, Sheffali (Ann Indian Acad Neurol, 2016)
An epileptic seizure is defined as transient occurrence of signs and/or symptoms due to abnormal excessive or synchronous neuronal activity in brain. There are diverse etiologies for acute seizure in infants and children. The present review provides a broad approach to diagnosis and treatment plan for acute seizure in children. The approach to a child with acute seizure is discussed with special emphasis on clinical approach based on history and focused examination with judicious choice of investigation and further management plan. The review also emphasizes on recognizing common nonepileptic events that masquerade as true seizure among infants and children.